Analisis Pengaruh Harga, Kualitas Layanan Dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Pada E-Commerce Shopee (Studi Mahasiswa FEB Jurusan Manajemen Universitas Islam Malang) - Mukti, Shinta Aulia Cahya; Sunaryo, Hadi; Mustapita, Arini Fitria (UNIVERSITAS ISLAM MALANG, 2025)
Abstract This research was conducted to determine and analyze the influence of price, service quality and customer satisfaction on customer loyalty on Shopee e-commerce. This type of research uses an explanatory research method through a quantitative approach, with the data analysis technique used, namely multiple linear regression analysis. Sampling was taken using non-probability sampling with a snowball sampling method with a total of 82 respondents who were students majoring in management at the Faculty of Economics and Business and had made at least 2 purchases at e-commerce Shopee. The results show that price, service quality and customer satisfaction have a simultaneous effect on customer loyalty and each independent variable, price, service quality and customer satisfaction have a partial effect on customer loyalty. Keywords: Price, service quality, customer satisfaction, customer loyalty